ADNP promotes neural differentiation by modulating Wnt/β-catenin signaling - Xiaoyun Sun (Nature Portfolio, 2020)
ADNP has been connected to neural developmental disorders. Here, the authors uncover a role for ADNP in neural induction and differentiation via β-Catenin stabilization, with ADNP disruption in zebrafish leading to defective neurogenesis and decreased Wnt signaling.